Evaluating the Economic Impact of Indonesia’s Public Policy Reforms on SMEs in the New Capital City - Yusuf, Khanan; Maulana, Supriyadi; Cahayani, Agustin (Cognitionis Civitatis et Politicae, 2024)
The Indonesian government has announced plans to move the country’s capital from Jakarta to the Benua Etam region. The main objective of the move is to reduce the burden on overpopulated Jakarta, as well as to flatten economic and infrastructure development to the eastern region of Indonesia. The existence of the Capital City of the Archipelago (IKN) in East Kalimantan offers great potential to strengthen the Micro, Small and Medium Enterprises (MSMEs) ecosystem in the region. As a new center of government designed to offset the burden of central Jakarta, IKN Nusantara can be a catalyst for the growth and sustainability of MSMEs, and strengthen their contribution to the national economy. This study aims to evaluate the economic impact of public policy reforms in Indonesia on MSMEs in the new IKN. The results of this study are expected to provide a clear picture of the economic impact of public policy reforms in Indonesia on MSMEs in the new IKN, as well as assist the government and MSME businesses in designing more effective policies and optimizing the potential of MSMEs in the region.